Sustainable road alignment planning in the built environment based on the MCDM-GIS method. (December 2022) - Jiang, Feng; Ma, Ling; Broyd, Tim; Chen, Ke; Luo, Hanbin; Pei, Yang
Highlights: Traffic, land use, demolition, noise, air pollution, and construction costs are considered. Road width, new road construction, and existing old road widening are considered simultaneously. Various methods are proposed to digitalise and parse factors into understandable expressions. Based on the MCDM-GIS method, the least-cost wide path algorithm is employed for road planning. Abstract: Sustainable road planning in the cities' built-up areas strives to meet traffic demands of society within limited spaces available for construction and various constraints in the built environment considering engineering, traffic, economic, social, and environmental factors. Unlike rural areas, road planning in the built environment can be significantly influenced by the surroundings, such as existing buildings, road network, and land use, and should consider noise and air pollution impact on residents. In addition, road width and road widening are significant factors for road alignment planning. Based on the MCDM-GIS method, the least-cost wide path algorithm is employed for sustainable road alignment planning in the built environment, considering building demolition and land use, traffic congestion, noise impact, air pollution impact, and construction costs. Road width, new road construction, and existing road widening are considered simultaneously. Several methods are proposed to digitalise and parse various sustainable factors into understandable expressions for road alignment planning. Forbidden areas and road buffer areas for road widening are defined. The proposed method is implemented in road planning in Dartford, Kent County, UK. Sustainable factors with different weights can generate various road alignments from different perspectives, and road widths can significantly and locally influence road alignments.